Preserving Regional Culture Through Paper Pulp Mask Workshop: Pelestarian Budaya Daerah Melalui Workshop Topeng Bubur Kertas - Moch. Irsyadul Ibad; Adisha Nur Izzatil M.; Vita Prihatiningsih; Cantika Fildzah F.; Ifit Novita Sari (Universitas Lancang Kuning, 2024)
The preservation of regional culture through this porridge mask workshop is carried out based on the results of our observations both directly and indirectly in the field, because of the lack of public concern, especially the younger generation to preserve this mask culture. In addition, researchers have also concluded that one of the main problems is the high cost of mask-making materials which causes a decrease in public enthusiasm. Therefore, researchers chose this topic to be explored and observed further so that the workshop on preserving the culture of this region can be carried out. In this service, researchers chose the Bina Daya scheme which is more specifically focused on fostering a culture being developed in the community by targeting students as the younger generation. We aim to use recycled paper that becomes waste as the main material. As a result, students are very enthusiastic to take part in this workshop because they can learn new things related to the innovation of making masks made from paper pulp that are environmentally friendly and have economic value.